India-Israel Relations: The Collaboration And Cooperation - Sharma, Madhubala; Sharma, Madhubala (International Journal of Psychosocial Rehabilitation, 2018)
India and Israel are the two oldest civilizations, India favours a multi-polar world where as Israel favour sauni-polar world.The official diplomatic relations between Israel and India were established in 1992. Their establishment ended a four decades period of only non-official relations between the countries. Despite its anti-Zionist and pro-Arab attitude, which was expressed in its reluctance to recognize the Jewish state, India eventually did recognized Israel in 1950. However, that recognition was not followed by a normalization of the relations between the states. Today India and Israel collaborate in defence, trade, strategic, and intelligence and security-related areas and the relationship is likely to become broader and more comprehensive over the long term, encompassing research, development and co-production in the defence sector, water resource management, science and technology, bilateral trade, and the non-defence sector. Based on a broad convergence of security, geopolitical and economicinterests, this evolving partnership represents Delhi’s shift from hostility towards the Jewish state to a more pragmatic and realistic approach.